Enhancing the ductility of laser-welded copper-aluminum connections by using adapted filler materials - Weigl, M.; Albert, F.; Schmidt, Michael (Physics Procedia, 2011)
Laser micro welding of direct copper-aluminum connections typically leads to the formation of intermetallic phases and an embrittlement of the metal joints. By means of adapted filler materials it is possible to reduce the brittle phases and thereby enhance the ductility of these dissimilar connections. As the element silicon features quite a well compatibility with copper and aluminum, filler materials based on Al-Si and Cu-Si alloys are used in the current research studies. In contrast to direct Cu-Al welds, the aluminum filler alloy AlSi12 effectuates a more uniform element mixture and a significantly enhanced ductility. © 2011 Published by Elsevier Ltd.
Created from Fastlane, Scopus look-up
Keywords: Aluminum; Copper; Filler material; Laser; Micro welding